Anti-candidal effect of endophytic fungi isolated from Calotropis gigantea - Nath, Archana (Universidad de Costa Rica, 2017)
Candida albicans is a most common cause of fungal infections in animals and birds. Understanding the increasing resistance of C. albicans to various antifungal therapeutic agents is important to discover new anti-candidal alternatives. The present study investigated the anti-candidal potential of five endophytic fungi extracts, isolated from the tropical ethnoveterinary plant, Calotropis gigantea. We firstly evaluated the in vitro antifungal activities of endophytic fungi extracts by the well diffusion method. Secondly, the cells of C. albicans were treated with the potent extract to observe significant ultrastructural changes. To further investigate the in vivo antifungal activity of the extract, some laboratory experiments with mice were undertaken, and posteriourly, the different organs were studied under the electron microscope for any deformities. Phomopsis asparagi showed the best anti-candidal activity with a minimum inhibitory concentration (MIC) of 46.9 µg/mL. The fungal test pathogen (C. albicans) exhibited various cell deformities when treated with the extract of P. asparagi.Histopathological studies of the vital organs of mice treated with the potent fungal extract did not show any significant pathological conditions when viewed under scanning electron microscope. Thus, P. asparagi can be a potential candidate for anti-candidal agents against C. albicans. Future studies will focus on the isolation of the bioactive components of the extract.